2018
DOI: 10.1016/j.jssr.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Elementary students’ challenges with informational texts: Reading the words and the world

Abstract: The purpose of this study is to describe ways in which elementary students access information from various components of informational social studies texts in schools. Although the time devoted to elementary social studies has decreased considerably in recent years, a renewed focus on content-area literacy skills, driven by state standard initiatives, presents us with the opportunity to regain lost social studies instructional time by integrating social studies content during literacy instructional time. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…To be sure, there is a danger in simply giving students a data visualization and expecting them to be able to read it. Research tells us that although it is often assumed that data visualizations are easy to read, students can face significant challenges when trying to make sense of them (Brugar and Roberts, 2018; Shreiner, 2019). And different types of data visualizations present their own unique challenges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be sure, there is a danger in simply giving students a data visualization and expecting them to be able to read it. Research tells us that although it is often assumed that data visualizations are easy to read, students can face significant challenges when trying to make sense of them (Brugar and Roberts, 2018; Shreiner, 2019). And different types of data visualizations present their own unique challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Data literacy is not a set of skills students will acquire on their own. Reading data visualizations, whether timelines, maps or graphs, is challenging and requires that students take stock of all the visual elements present in a data display, make connections between visual elements to extract information, and understand the data's referents and context in order to draw conclusions or make inferences (Brugar and Roberts, 2018;Duke et al, 2013;Maltese et al, 2015;Roberts et al, 2013;Shah and Hoeffner, 2002;Shreiner, 2019). Although students can face challenges when trying to read data visualizations, they offer multiple benefits to learning.…”
mentioning
confidence: 99%
“…Everything is possible." In a study conducted by Brugar and Roberts (2018), it was determined that if students cannot find the correct answer within the text, they tend to write random words from the text, or depend only on their prior knowledge, or to give incorrect answers depending on the source. In this study, it was seen that the 5 th grade students have a similar tendency.…”
Section: Discussionmentioning
confidence: 99%
“…This impressive array of data visualizations will no doubt overwhelm the typical student, particularly if they have never developed a foundational knowledge for making sense of simpler forms. A wealth of research (Brugar and Roberts, 2017; Duke et al , 2013; Maltese et al , 2015; Roberts et al , 2013; Schnotz, 2002; Schnotz and Bannert, 2003; Schnotz et al , 2014; Shah and Hoeffner, 2002; Shah et al , 1999) has indicated that data visualizations are challenging to understand and integrate with other information. These challenges will likely increase when there exists such a multitude of forms for readers to unpack.…”
Section: Related Literaturementioning
confidence: 99%